Processing Map and Hot Deformation Behavior of Mo-Nb Single Crystals. Issue 2 (February 2018) - Wen, Zhang; Xuanqiao, Gao; Jun, Cheng; Zhongwu, Hu; Laiping, Li; Bin, Zhao; Pingxiang, Zhang
Abstract: The processing map of Mo-Nb single crystals was established on the base of Prasad instability. The hot deformation behavior of Mo-Nb single crystals has been characterized through stress-strain curves and processing map in the temperature range of 1100∼1300 °C and strain rate range of 0.001∼10 s −1 . The results indicate that the flow stress is affected significantly by deformation temperature and strain rate during the hot deformation of Mo-Nb single crystals. Based on the processing map, the optimum condition for hot deformation of Mo-Nb single crystals is in the region of high temperatures (>1190 °C) and high strain rates (>3.16 s −1 ). Microstructure observation of deformed specimens at different deforming conditions shows that lots of orthogonal cracks, which result from the movement of dislocations along with the glide planes, are observed in specimens deformed at 1100 °C/0.01 s −1 and 1150 °C/10 s −1 . Less cracks can be observed in specimens deformed at 1250 °C/0.01 s −1, and few cracks are found in specimens deformed at 1300 °C/10 s −1 . The XRD result shows that the specimen deformed at 1300 °C/10 s −1 retains single crystal structure, indicating that the specimen does not undergo instability of flow during hot deformation, which are in good agreement with the results of Mo-Nb single crystals predicted from processing map.